2003
DOI: 10.1002/cne.10640
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory circuitry involving Y cells and Y retinal terminals in the C laminae of the cat dorsal lateral geniculate nucleus

Abstract: We previously established (Datskovskaia et al. [2001] J Comp Neurol 430:85-100) that roughly 40% of Y retinal terminals contact interneurons in the A lamina of the dorsal lateral geniculate nucleus (dLGN) of the cat. However, we did not establish whether the dendritic terminals of interneurons postsynaptic to Y retinal terminals subsequently contact Y thalamocortical cells. To begin to address this issue, we examined the synaptic targets of Y retinal terminals in the magnocellular C lamina of the dLGN, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 81 publications
(191 reference statements)
2
14
0
Order By: Relevance
“…Intrageniculate inhibition clearly plays an important role in receptive-field construction within dLGN, although it is unlikely that it could explain the differences in response latency and receptive-field size of Y A and Y C cells (Table 2). Although the intrageniculate inhibitory circuitry is known to differ between layer A and layer C, it is thought to be similar for Y A and Y C cells (Dankowski and Bickford 2003;Datskovskaia et al 2001). Moreover, although systematic differences in intrageniculate inhibition would make Y A and Y C cells different in the strength of their receptive-field surrounds, response gains, offsets, and mean firing rates (Bonin et al 2005), none of these differences was revealed by our measurements (Figs.…”
Section: Neuronal Mechanisms Underlying Y a -Y C Receptive-field Mismmentioning
confidence: 49%
“…Intrageniculate inhibition clearly plays an important role in receptive-field construction within dLGN, although it is unlikely that it could explain the differences in response latency and receptive-field size of Y A and Y C cells (Table 2). Although the intrageniculate inhibitory circuitry is known to differ between layer A and layer C, it is thought to be similar for Y A and Y C cells (Dankowski and Bickford 2003;Datskovskaia et al 2001). Moreover, although systematic differences in intrageniculate inhibition would make Y A and Y C cells different in the strength of their receptive-field surrounds, response gains, offsets, and mean firing rates (Bonin et al 2005), none of these differences was revealed by our measurements (Figs.…”
Section: Neuronal Mechanisms Underlying Y a -Y C Receptive-field Mismmentioning
confidence: 49%
“…Y cells are located in the C m , and the dendrites of A laminae Y cells cross laminar borders, whereas the dendrites of X cells are confined to the lamina of origin (Friedlander et al, 1981;Stanford et al, 1983;Wilson et al, 1984). Although the triadic arrangements of RLD profiles might imply an association with X cells (which have been suggested to be the primary target of interneurons; Sherman and Friedlander, 1988), we have found that Y retinogeniculate axons contact interneurons and that glomeruli are particularly prominent in the C m , where X cells are absent (Datskovskaia et al, 2001;Dankowski and Bickford, 2003). Thus, RLD profiles could primarily participate in circuitry involving Y cells.…”
Section: Distribution Of Rld Profiles In the Dlgnmentioning
confidence: 83%
“…In cat tissue, this antibody has been shown to stain axon thalamic terminals originating from the basal forebrain, thalamic reticular nucleus (TRN)/PGN, and pretectum (Bickford et al, 1994;Wang et al, 2001Wang et al, , 2002a as well as the dendritic terminals of dLGN interneurons Datskovskaia et al, 2001;Dankowski and Bickford, 2003).…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…In the cat's dLGN, intemeurons were thought to be mostly associated with the X pathway (Sherman and Friedlander, 1988). However, subsequent studies showed that nearly half of the synaptic targets of Y retinogeniculate terminals are intemeurons, and intemeurons contact the dendrites of Y relay cells (Datskovskaia et aI., 2001;Dankowski and Bickford, 2003). All intemeurons are GABAergic, and their outputs inhibit postsynaptic targets (Montero, 1987;Guillery et aI., 2001).…”
Section: Types Of Thalamic Cellsmentioning
confidence: 99%